INVESTIGATING THE THE EFFECT OF BROAD MONEY SUPPLY ON ECONOMIC GROWTH IN ALGERIA: FRESH INSIGHTS FROM AUGMENTED LINEAR & NONLINEAR ARDL (1970-2021) - Senouci Bereksi, Dr. Imane; Attouchi, Dr. Manel; Benbouziane, Dr. Fatima (The journal of contemporary issues in business and government, 2024)
This study investigates the asymmetric Effect of Broad Money Supply Shocks on Economic Growth in Algeria using time-series data from 1970 to 2021. The study has employed a novel extension of ARDL which is Augmented ARDL & Augmented NARDL. The result reveals that adjustments in broad money supply influence Algeria’s economic growth asymmetrically in both short & long run. As a consequence, positive (negative) money supply shocks boost (decrease) the economic growth rates. These findings strongly imply that money is not neutral, and this could be regarded as a realization goal of monetary policy. While, even though the efforts made by policymakers to stimulate high levels of economic growth, the aim of improvement is also modest compared with other developing countries.